ERAS & YMGS share geotechnical expertise via Career Day Programme - Safuan, Shariff; Mohd Hashim, Mohd Saad (2019)
To highlight the important roles that future engineers have to shoulder, the Earth Resources & Sustainability Centre (ERAS) of Universiti Malaysia Pahang (UMP), in collaboration with the Youth Wing of Malaysian Geotechnical Society (YMGS), recently organized a Career Day Programme at the Astaka Hall of the former’s campus in Gambang.